Nutritional assessment of Chinese gynecologic cancer survivors with post-surgical lower limb lymphedema: a cross-sectional study - Zhu, Xiaoling; Liu, Xinjun; Tian, Jinbo; He, Chunshui; Huang, Shan (Frontiers in Nutrition, 2024)
Objective: This study aims to evaluate the nutritional status of Chinese gynecologic cancer survivors with post-surgical lower limb lymphedema (LLL) by analyzing serum albumin levels and the prognostic nutritional index (PNI).: A retrospective cross-sectional study was conducted at two Chinese medical centers. The cohort comprised 155 gynecologic cancer survivors who developed symptomatic unilateral LLL post-surgery, during the period from September 2021 to June 2024. Nutritional status was assessed by measuring serum albumin and PNI. Statistical analysis was performed using univariate and multivariate logistic regression models to identify factors associated with low serum albumin and PNI. Univariate and multivariate logistic regression analyses were performed to identify factors associated with low serum albumin and PNI.The mean age of the cohort was 55.47 ± 10.56 years, and the median total survival time was 72.0 months (36.5, 111.5 months). The prevalence of low serum albumin (<40 g/L) was 40.0%, and low PNI (<45) was 80.6%. Significant associations were found between low hemoglobin levels and both low serum albumin (OR = 1.05, 95% CI: 1.02-1.08, p<0.001) and low PNI (OR = 1.09, 95% CI: 1.04-1.13, p<0.001). Advanced International Society of Lymphology stage 3 was also associated with low albumin (OR = 0.18, 95% CI: 0.03-0.99, p<0.05).The study highlights a significant prevalence of high risk of malnutrition among Chinese gynecologic cancer survivors with LLL, underscoring the need for regular nutritional assessments and interventions.